An Enhanced Modified Multiport Interleaved Flyback Converter for Photovoltaic-Shunt Active Power Filter (PV-SHAPF) Applications - Radhamani Rajakkannu; Balamurugan Rangaswamy (International Transactions on Electrical Energy Systems)
This paper presents a newly designed modified multiport interleaved flyback converter (MMPIFC) to transfer the photovoltaic (PV) power to the DC bus of the parallel-connected multilevel inverter-based shunt active power filter (SHAPF). The proposed modified multiport interleaved flyback converter (MMPIFC) is designed to interconnect N number of input power sources into the DC bus of the SHAPF to fix the problems with the partial shadow and improve the SHAPF’s ability to compensate. Compared to the commonly used interleaved flyback converter (IFC), the proposed MMPIFC has a larger boost factor toward the DC voltage input. The flow of power between the different power sources and SHAPF is controlled by varying the duty ratio of the main switches. The working principles of the proposed MMPIFC-operated PV-SHAPF are explored in this paper, and essential design concerns are highlighted. A prototype model with 1 kVA, 400 V, and 50 HZ is built and tested under various conditions to validate the theoretical analysis, design, and control method.